Digital computer process control. - Ching, Alan Kwok-Keung. (University of Ottawa (Canada), 1977)
A shell and tube heat exchanger was interfaced with a NOVA digital computer to allow automatic data logging and direct digital computer control. A real time computer operating system was developed for this special application. The Characteristics of a non-linear Multiplicative control algorithm were studied using this system. As a result of the study, a feed back loop was added to the Multiplicative control algorithm to compensate the offset caused by the non-linear characteristics of the heat exchanger. The stability region of the Multiplicative control algorithm was mapped and showed high and low stability limits for Multiplicative gain settings.
Keywords: Engineering, Chemical.